The Role of FOXO3 and Irisin in Evaluating Posterior Cruciate Ligament and Knee Functional Recovery After Surgical Treatment of Tibial Avulsion Fracture of the Posterior Cruciate Ligament Insertion - Shen, Wenbin; Xiao, Yao; Yu, Xin; Zhang, You (Journal of Medical Biochemistry, 2025)
Objective: To explore the predictive value of serum forkhead box protein O3 (FOXO3) and Irisin in evaluating posterior cruciate ligament (PCL) and knee functional recovery after surgical treatment of tibial avulsion fractures (TAFs) of the PCL insertion (PCL-TAFs).Methods: In this prospective cohort study, we recruited 125 patients with PCL-TAFs (research group) and 111 healthy controls (control group) between October 2023 and December 2024. Serum FOXO3 and Irisin levels were detected at preoperative baseline and 6-month follow-up. Clinical evaluations included Lysholm scores, knee joint range of motion (ROM), posterior drawer testing, and International Knee Documentation Committee Subjective Knee Form (IKDC) scores. Pearson correlation and ROC analyses examined biomarker associations with functional recovery.Results: PCL-TAF patients exhibited higher preoperative FOXO3 levels than controls, which decreased following treatment (P < 0.05). Conversely, Irisin levels were initially lower than controls but increased post-treatment (P < 0.05). The predictive performance of combined FOXO3 and Irisin yielded 70.59% sensitivity and 94.51% specificity for detecting posterior drawer test positivity (AUC=0.880). FOXO3 and Irisin together could identify severe dysfunction (IKDC III-IV) with 75.76% sensitivity and 77.17% specificity (AUC=0.784).Conclusion: Serum FOXO3 and Irisin show clinical utility as potential biomarkers for functional recovery monitoring following PCL-TAF surgery, providing an objective molecular basis, as evidenced by ROC analysis, for the formulation of individualized rehabilitation plans.